2010
DOI: 10.1007/s10482-010-9539-9
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance of Mesorhizobium type strains to different environmental stresses

Abstract: The symbiosis between rhizobia and legumes is affected by different environmental conditions. Our aims were to evaluate stress tolerance of Mesorhizobium species and investigate species-specific stress response mechanisms. Tolerance of Mesorhizobium type strains to temperature, salt and pH stress was evaluated. Mesorhizobium thiogangeticum showed highest growth with 1.5% NaCl and Mesorhizobium ciceri at pH 5. Mesorhizobium plurifarium showed higher growth at 37°C. SDS-PAGE analysis revealed changes in the prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
36
0
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(40 citation statements)
references
References 55 publications
(50 reference statements)
3
36
0
1
Order By: Relevance
“…A previous study showed that this strain is tolerant to heat shock and cold conditions, and grows well at pH 5. 30 …”
Section: Introductionmentioning
confidence: 99%
“…A previous study showed that this strain is tolerant to heat shock and cold conditions, and grows well at pH 5. 30 …”
Section: Introductionmentioning
confidence: 99%
“…Effect of temperature on symbiotic nitrogen fixation. Unfavorable temperatures impair nodulation and nitrogen fixation resulting in low solute production, transportation and synthesis of various heat and cold-shock proteins compared to susceptible strains(Alexandre and Oliveira 2011;Laranjo and Oliveira 2011). The GroEL…”
mentioning
confidence: 99%
“…Members of the genus Mesorhizobium can establish a nitrogen-fixing symbiosis with legume species found in many environments, including tropical, subtropical, temperate, and arctic areas (3). This large distribution suggests their adaptation to several ecoclimatic conditions (4, 5). Many different legume species have now been studied and shown to play several ecological roles which are essential to environmental sustainability.…”
Section: Genome Announcementmentioning
confidence: 95%